METHODS FOR ASSESSING AND MONITORING PHYSICAL FITNESS IN WOMEN - Buronova Sidiqa Tuxtayevna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the methods for assessing and monitoring physical fitness in women. It analyzes various evaluation techniques, including tests for cardiovascular endurance, muscular strength, flexibility, and body composition, as well as strategies for tracking progress over time. The study emphasizes the importance of individualized assessment, systematic monitoring, and evidence-based approaches to optimize training programs, improve performance, and maintain long-term health outcomes.